To solve the equation 5b - 12 = 3, we need to isolate the variable b.
First, we add 12 to both sides of the equation to get rid of the constant term -12:
5b - 12 + 12 = 3 + 12
5b = 15
Next, we divide both sides of the equation by the coefficient 5 to solve for b:
5b/5 = 15/5
b = 3
Therefore, the solution to the equation 5b - 12 = 3 is b = 3.
Solve this equation
5b-12=3
3 answers
Thanks for your help in this equation
You're welcome! I'm glad I could help. If you have any more questions, feel free to ask.